Model simplification of coal combustion kinetics: a case study of Weihuliang coal in Urumchi, China. Issue 6 (2nd November 2019) - Su, Hetao; Ji, Huaijun; Chen, Xiaoyu
Abstract : The present study reports the determining the evolution stage of coal combustion bases on its corresponding characteristic behaviours and the oxidation kinetics during different evolution stages including the newly ignited stage (NIS), accelerating stage (AS), consistently burning stage (CBS), slowly burning-out stage (SBS), and extinct stage (ES). The main characteristic behaviours during coal combustion, namely, temperature gradients, oxygen consumption, gaseous products, and heat release, were investigated using an experimental apparatus. Preliminary criteria for distinguishing the evolution stage of a coal fire were developed based on these characteristic behaviours. The results showed that for the Weihuliang coal, the CO/CO2 ratio could be regarded as an indicator of an extinct coal fire, and SO2 could be used to distinguish newly ignited, accelerating, or consistently burning coal fires. The heat release during the CBS, SBS, and ES was classified into three heat levels, with the first-level heat occurring during the CBS, second-level heat during the SBS, and third-level heat during the ES. A minimum value of oxygen mass flux required for ideal coal combustion was proposed to ensure the applicability of the first-order Arrhenius equation during the ES. Lastly with the oxygen supply considered, unifying the first-order Arrhenius equations (the chemical equations) during different evolution stages was put forward as an approach of model simplification. This work will be helpful in the understanding the evolution process of coal fires, and also useful for the effective control and sustainable recovery utilisation of coal fires.